Hamming Distance for the Trellis Coded Block Codes and Applications in Bit Error Rate Too - Thelapolu Nikitha, Naluguru Udaya Kumar, Shijin Kumar P.S (International Journal of Advanced Science and Technology, 2020)
This research paper proposes the Trellis Coded Modulation (TCM) scheme that is built from Linear Block Codes (LBC)